Saberes docentes e atuação profissional: estudo de caso com egressos do “PIBID Biologia-Alegre” do CCENS/UFES. - Lopes, Talita Molina (2020)
The Institutional Teaching Initiation Scholarship Program (PIBID) was created in 2007 by the Ministry of Education and administered by the Coordination for the Improvement of Higher Education Personnel (CAPES), with the main objective of contributing to the enhancement and encouragement of the teaching career through the insertion of future teachers into the school environment. Therefore, it is believed that the activities experienced through PIBID enable future teachers to build the main teaching knowledge necessary for professional performance. Thus, the objective of this study was to analyze the main teaching knowledge built during the activities developed by graduates of the subproject “PIBID Biologia-Alegre” at the Center for Exact, Natural and Health Sciences (CCENS) of the Federal University of Espírito Santo (UFES). The research was guided by the qualitative approach, through a case study. Data collection was carried out using questionnaires and semi-structured interviews. The information narrated in the interviews was analyzed using the Content Analysis technique, more specifically by categorization, based on four categories: knowledge of professional training; disciplinary knowledge; curricular knowledge and; experiential knowledge, derived from the classification of teaching knowledge defined by Maurice Tardif (2012). The analysis of the information narrated in the interviews indicated the construction of the main teaching knowledge based on the experiences reported by the graduates of “PIBID Biologia-Alegre”. Still, it was found that the construction of this knowledge allowed the teaching profession to be reframed, allowing the understanding of the importance of activities that help the function, such as planning; the use of different teaching methods and/or resources; curricular and scientific knowledge and; the interaction with students and other subjects that make up the school environment. Participation in PIBID has helped and continues to assist teaching practice, contributing to a change in conception about teaching and knowledge of the reality of the school environment. In this perspective, PIBID increasingly becomes a formative space that enables the construction and development of teaching knowledge essential to practice